Moon's cloud blanket - St. Romain, Rose Anne (Pelican Pub. Co., 2003)
In this retelling of a Native American tale, the Moon weaves a blanket of clouds around a mother and her children who are freezing atop a cypress tree, having sought shelter from a flood.